2013
DOI: 10.3390/md11041203
|View full text |Cite
|
Sign up to set email alerts
|

A Therapeutic Potential for Marine Skeletal Proteins in Bone Regeneration

Abstract: A vital ingredient for engineering bone tissue, in the culture dish, is the use of recombinant matrix and growth proteins to help accelerate the growth of cultivated tissues into clinically acceptable quantities. The skeletal organic matrices of calcifying marine invertebrates are an untouched potential source of such growth inducing proteins. They have the advantage of being ready-made and retain the native state of the original protein. Striking evidence shows that skeleton building bone morphogenic protein-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 67 publications
0
33
0
1
Order By: Relevance
“…Protocols are well established now for the mass production of new proteins using a combination of site random mutagenesis followed by high-throughput screening (Kim, 2008;Green et al, 2013). This is an attractive proposition.…”
Section: Growing Biomaterials With Living Cellsmentioning
confidence: 99%
“…Protocols are well established now for the mass production of new proteins using a combination of site random mutagenesis followed by high-throughput screening (Kim, 2008;Green et al, 2013). This is an attractive proposition.…”
Section: Growing Biomaterials With Living Cellsmentioning
confidence: 99%
“…For this reason, apoptosis is another tightly regulated mechanism triggered during a defence state and histolysis, or purposely targeting unneeded or lessspecialized cells (Kiss, 2010). Furthermore, the structure of the ECM constitutes a dynamic scaffold-based circuitry with integrative components that promote cellular proliferation, migration, and tissue motion (Green et al, 2013). As a result, muscle (Dyachuk, 2013) and neural (Odintsova et al, 2010) cell differentiation depend on functional peptides and growth factors found in the ECM, which constitute basic requirements for muscle assembly, neural guidance, and synaptogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Another down-regulated gene codes for a protein containing a platelet-derived growth factor domain, though the regulation of this kind of protein upon exposure to low pH has not been previously reported in corals. However, it is already known that homologs of human bone-morphogenesis proteins (BMP2/4) participate in skeleton production of marine calcifiers, including corals (Green et al, 2013). In fact, proteins carrying this domain are currently used for bone regeneration in humans, and its use, in combination with coral skeleton, has been proposed to treat bone defects (Parizi et al, 2012).…”
Section: Mild Stress Response Of the Coral To Low Phmentioning
confidence: 99%